Shared care plan: an extraordinary tool for the personalization of medicine and respect for self-determination - Bevilacqua, Greta; Bolcato, Matteo; Rodriguez, Daniele; Aprile, Anna (Acta Biomedica Atenei Parmensis, 2020)
BACKGROUND. On 22 December 2017, Law No. 219 was approved in Italy. This law provides citizens with effective tools with which to express healthcare decisions: namely, advance treatment directives (ATD) and shared care plans (SCP).METHODS. This article presents an analysis of 70 SCP cases carried out in a tertiary hospital in Italy during the period between 01.02.2018 and 29.02.2020 inclusive.RESULTS. In 90% of cases, the objective of the plan pertained to situations regarding patients’ refusal of transfusions of blood components, the majority (97%) due to their belonging to the religious movement of Jehovah’s Witnesses. 46% of the sample had drafted ATDs. The course of treatment recommended by the attending physicians was confirmed in 93% of the SCP cases. Trustees were appointed in 96% of cases. In 55% of cases, patients assigned trustees with attestative functions and the remaining 45% with creative functions. The results demonstrate that each patient personally dictates his or her wishes and the role assigned to the trustee. SCP meetings serve as a useful tool for providing the patient and his or her relatives with information, and for appointing a trustee. However, it has never been necessary to solicit the intervention of the trustee following a surgical operation.CONCLUSIONS: The SCP has proven to be an essential tool in achieving the objective of personalised medicine. However, there is still notable passivity in its application. Further effort is required in order for it to become a common asset in clinical practice.